(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Maintenance is the important phase in software development lifecycle which initiates after the software has been deployedÂ for use. Reusability is an important area of concern which depicts the extent to which a module can be used again inÂ different applications with slight or no modification. Maintainability is one of the contributing factors for assessingÂ Reusability. So, assessment of Reusability is preferred over Maintainability.Â This paper has been split into Introduction, Role of Maintainability, Role of reusability and conclusion. In the introduction section the concept that how the software evolves has been discussed. The second section focuses on the Role of Maintainability. The third second emphasizes on the Role of Reusability within the domains of Object-OrientedÂ Programming and Aspect-Oriented Programming. In the last section we have concluded that assessment of ReusabilityÂ must be given more preference over the assessment of Maintainability.